(untitled) (Nexo Revista Científica, 2023)
Horizontal shell and tube condensers are widely used in several industrial applications due to its versatility and heat transfer efficacy. In the present work, the thermo-hydraulic design of a horizontal shell and tube heat exchanger intended to condense 25,000 kg/h of a pure ethanol stream was carried out. Several key design parameters were calculated such as the number of tubes, heat transfer area, overall heat transfer coefficient, shell internal diameter, baffle spacing, as well as the pressure drop for both streams. The heat exchanger type is of pull-through floating head, and will present a number of tubes of 731, a heat transfer area of 223.68 m2, an overall heat transfer coefficient of 499.36 W/m2.ºC, a shell internal diameter of 1.684 m and a baffle spacing of 0.674 m. Around 157 kg/s of chilled water will be required for this heat transfer service. The values of both the shell side (10,069.25 Pa) and tube side (42,192.63 Pa) pressure drop are below the maximum values set by the process.